Inflammatory Cellular Response to Mechanical Ventilation in Elastase-Induced Experimental Emphysema: Role of Preexisting Alveolar Macrophages Infiltration. (19th December 2018) - Rouze, Anahita; Voiriot, Guillaume; Guivarch, Elise; Roux, Françoise; Tran Van Nhieu, Jeanne; Isabey, Daniel; Brochard, Laurent; Maitre, Bernard; Mekontso-Dessap, Armand; Boczkowski, Jorge
Abstract : An excessive pulmonary inflammatory response could explain the poor prognosis of chronic obstructive pulmonary disease (COPD) patients submitted to invasive mechanical ventilation. The aim of this study was to evaluate the response to normal tidal volume mechanical ventilation in an elastase-induced murine model of pulmonary emphysema. In this model, two time points, associated with different levels of lung inflammation but similar lung destruction, were analyzed. C57BL/6 mice received a tracheal instillation of 5 IU of porcine pancreatic elastase (Elastase mice) or the same volume of saline (Saline mice). Fourteen (D14) and 21 (D21) days after instillation, mice were anesthetized, intubated, and either mechanically ventilated (MV) or maintained on spontaneous ventilation (SV) during two hours. As compared with Saline mice, Elastase mice showed a similarly increased mean chord length and pulmonary compliance at D14 and D21, while bronchoalveolar lavage cellularity was comparable between groups. Lung mechanics was similarly altered during mechanical ventilation in Elastase and Saline mice. Activated alveolar macrophages CD11b mid were present in lung parenchyma in both Elastase SV mice and Elastase MV mice at D14 but were absent at D21 and in Saline mice, indicating an inflammatory state with elastase at D14 only. At D14, Elastase MV mice showed a significant increase in percentage of neutrophils in total lung, as compared with Elastase SV mice. Furthermore, alveolar macrophages of Elastase MV mice at D14 overexpressed Gr1, and monocytes showed a trend to overexpression of CD62L, compared with Elastase SV mice. In an elastase-induced model of pulmonary emphysema, normal tidal volume mechanical ventilation may produce an increase in the proportion of pulmonary neutrophils, and an activation of alveolar macrophages and pulmonary monocytes. This response seems to be observed only when the emphysema model shows an underlying inflammation (D14), reflected by the presence of activated alveolar macrophages CD11b mid.